2012
DOI: 10.1051/0004-6361/201117815
|View full text |Cite
|
Sign up to set email alerts
|

Observational studies of Cepheid amplitudes

Abstract: Context. Physical and phenomenological properties (radius, luminosity, shape of the light curve, etc.) of Cepheids strongly depend on the pulsation period, with the exception of the pulsation amplitude. A possible factor causing a wide range of pulsation amplitudes might be the different atmospheric metallicities of individual Cepheids. Aims. We studied the influence exerted by the atmospheric iron content, [Fe/H], on the pulsational amplitude of Galactic Cepheids. Methods. We searched for correlations between… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
(33 reference statements)
1
16
1
Order By: Relevance
“…Since there are no spectroscopic [Fe/H] values for Cepheids In a recent study Majaess et al (2013) found that the peakto-peak amplitudes of long period extragalactic Cepheids are significantly smaller at lower [Fe/H] ratio. This is just the opposite of the behaviour of the peak-to-peak amplitudes of short period Galactic Cepheids (Szabados & Klagyivik 2012a) and the R 21 and R 31 Fourier parameters in this paper, also deduced for short period Cepheids. These results are however not in conflict with the theoretical calculations.…”
Section: An Outlook For Extragalactic Cepheidscontrasting
confidence: 66%
“…Since there are no spectroscopic [Fe/H] values for Cepheids In a recent study Majaess et al (2013) found that the peakto-peak amplitudes of long period extragalactic Cepheids are significantly smaller at lower [Fe/H] ratio. This is just the opposite of the behaviour of the peak-to-peak amplitudes of short period Galactic Cepheids (Szabados & Klagyivik 2012a) and the R 21 and R 31 Fourier parameters in this paper, also deduced for short period Cepheids. These results are however not in conflict with the theoretical calculations.…”
Section: An Outlook For Extragalactic Cepheidscontrasting
confidence: 66%
“…Berdnikov & Ivanov (1986) and Paczyński & Pindor (2000) corroborated the van Genderen (1978) conclusion concerning the amplitude-metallicity behavior of longer-period Cepheids. A recent analysis by Szabados & Klagyivik (2012) indicated that metal-poor classical Cepheids display slightly larger amplitudes than their metal-rich counterparts, a result inferred by correlating the latest abundance and photometric data for Galactic Cepheids (−0.4 [Fe/H] 0.4). Szabados & Klagyivik (2012) found the correlation strongest for shorter-period Cepheids, whereas the impact of metallicity on radial velocity and B-band amplitudes for longer-period Cepheids was less pronounced, and the coefficient for the latter was not significant (their Table 2 and Fig.…”
Section: Introductionmentioning
confidence: 84%
“…Araucaria photometry for Cepheids in NGC 6822 was published by Pietrzyński et al (2004). Following Klagyivik & Szabados (2009) and Szabados & Klagyivik (2012), peak-to-peak amplitudes were determined for the Cepheids (see also the pertinent discussion by Ngeow et al 2003). The period-amplitude results derived for the Galactic sample are similar to those found in the comprehensive analysis by Klagyivik & Szabados (2009).…”
Section: Photometrymentioning
confidence: 99%
“…In particular, Szabados & Klagyivik (2012), by using a large sample (327) of Galactic Cepheids with accurate pulsation parameters and spectroscopic metal abundances, found evidence that the luminosity and the radial velocity amplitudes slightly decrease with increasing iron abundance. However, no firm conclusion has been reached since Pedicelli et al (2010), by using a similar data set, did not find a clear dependence on metallicity.…”
Section: Luminosity Amplitudes and Metallicity Dependencementioning
confidence: 98%